From the Editor: Changes and new directions of Intangible Capital - Jose Maria Sallan (Intangible Capital, 2007)
In this editorial, I notify to the community the adoption of the Open Journal Systems platform as the publishing environment of Intangible Capital. I also give notice of the new initiatives that the editors of the journal will develop in the near future.